2022
DOI: 10.3390/life12010072
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chicken Immune Responses to Immunization with Vaccine La Sota or ZG1999HDS Strain of Newcastle Disease Virus

Abstract: Newcastle disease (ND) is a highly contagious avian disease. Global control of ND is mainly based on vaccination of poultry; however, reported outbreaks of ND in vaccinated flocks indicate a constant need to re-evaluate the existing vaccines and a development of the new ones. In this study, 4-week-old male chickens of the layer commercial hybrid were immunized oculonasally with a commercial NDV live La Sota vaccine (LS group), a suspension of lyophilized NDV strain ZG1999HDS (ZG group), or saline (Control (K) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…(2020). Administering a double dose of vaccination to a flock of chickens addresses the variability in immune responses, ensuring that even birds with weaker immune systems can develop protective immunity (Nedeljkovic et al., 2022; Illango et al., 2005; Sarba et al., 2021). This finding also supports previous study (Hu et al., 2022; Dimitrov et al., 2017; Miller et al., 2013; Ravikumar et al., 2022), which found that a double dose offers a higher concentration of antigens, boosting the possibility of a stronger and more effective immune response in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…(2020). Administering a double dose of vaccination to a flock of chickens addresses the variability in immune responses, ensuring that even birds with weaker immune systems can develop protective immunity (Nedeljkovic et al., 2022; Illango et al., 2005; Sarba et al., 2021). This finding also supports previous study (Hu et al., 2022; Dimitrov et al., 2017; Miller et al., 2013; Ravikumar et al., 2022), which found that a double dose offers a higher concentration of antigens, boosting the possibility of a stronger and more effective immune response in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…This Case Report reports on the use of NDV strain ZG1999HDS as an oncolytic agent in the treatment of OMM in a dog. The strain was reported to be mild, superior to La Sota strain of NDV as immunogenic and cytolitic agent for several tumour cells lines in vitro (FsaR -mouse fibrosarcoma, SC-CVII-mouse squamous cell carcinoma, CT26WTmouse colon adenocarcinoma, 4T1 -mouse breast adenocarcinoma) and in vivo (CT26WT and 4T1) (Nedeljković et al, 2022;Mazija et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Biosecurity involves various techniques, such as cleaning, disinfecting, preventing farm access by rodents and wild birds, and strict hygiene practices among visitors and farm staff [ 20 ]. In chickens vaccinated with a combination of live and inactivated vaccines, a strong level of immunity is exhibited compared with that in chickens receiving only live vaccines; meanwhile, genotype-matched vaccines provide better protective immunity than heterogeneous vaccine strains [ 21 ]. Live LaSota and B1 vaccines were first developed based on lentogenic NDV strains and are the vaccine strains that are most commonly used worldwide [ 22 ].…”
Section: Introductionmentioning
confidence: 99%